2008
DOI: 10.1097/01.prs.0000293754.55706.7f
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of Composite Tissue Allograft Survival by Immature Recipient Dendritic Cells Pulsed with Donor Antigen and Transient Low-Dose Immunosuppression

Abstract: Donor alloantigen-pulsed recipient bone marrow-derived dendritic cells combined with transient T-cell-directed immunosuppression significantly prolonged composite tissue allograft survival across a full major histocompatibility complex barrier. This may represent the basis for a novel, clinically applicable strategy to promote composite tissue allograft survival with reduced systemic immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 38 publications
0
32
1
2
Order By: Relevance
“…The protocol is similar to earlier work of ours [15], but we tested different major histocompatibility complex complete mismatch rodent stains model and modified the DC injection timing to induce immune tolerance. The reasons that lacking of the comparative group to look at low-dose CsA and ALS without DCs because our past study has demonstrated that combination of low-dose CsA and ALS did not show significant increase the allograft survival, as compared to that of ALS alone or CsA monotherapy [15]. This study did not include the syngeneic transplants group because we have already done syngeneic transplant before we did allogeneic CTA studies.…”
Section: Experimental Designsmentioning
confidence: 93%
See 2 more Smart Citations
“…The protocol is similar to earlier work of ours [15], but we tested different major histocompatibility complex complete mismatch rodent stains model and modified the DC injection timing to induce immune tolerance. The reasons that lacking of the comparative group to look at low-dose CsA and ALS without DCs because our past study has demonstrated that combination of low-dose CsA and ALS did not show significant increase the allograft survival, as compared to that of ALS alone or CsA monotherapy [15]. This study did not include the syngeneic transplants group because we have already done syngeneic transplant before we did allogeneic CTA studies.…”
Section: Experimental Designsmentioning
confidence: 93%
“…Hindlimb transplantation was performed on the rats according to previously described procedures [15]. Anesthesia was administered via an i.p.…”
Section: Animal Model Of Orthotopic Hindlimb Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Free flaps have been reported for composite reconstruction including the latissimus dorsi; however, the extent of the procedure and the intraoperative repositioning were challenging in this case. The bioprosthetic mesh has been used in combination with flaps because it provides fascial or musculofascial substitution only [3,5]. The VMG is a relatively easy and quick procedure that provides a reliable reconstructive option with minimal functional deficit.…”
Section: Discussionmentioning
confidence: 99%
“…All animals in the control group and experimental group (n ϭ 6 per group) received orthotopic hind limb transplantation from BN to LEW, as previously described, with end-to-end anastomosis of the femoral vessels and sciatic nerve. 19 After re-establishing blood flow, the host and donor sciatic nerve stumps were tightly approximated with epineurial neurorrhaphy using 10-0 nylon suture. Each animal of the experimental group then received an injection of 1.5 U/20 L chondroitinase ABC in vehicle (1% bovine serum albumin in phosphate-buffered saline) directly into the sciatic nerve at the suture line using a 30-gauge needle.…”
Section: Hind Limb Transplantationmentioning
confidence: 99%